Dietary Diversity Score and Adolescent Obesity Among West Sumaterans Girl - Susmiati, susmiati; INDRAWATY LIPOETO, Nur; KHAIRINA, Ilfa (Nutrición Clínica y Dietética Hospitalaria, 2024)
Backbround: Obesity develops from multifactorial factors. Adequacy and quality of food are associated with nutritional needs and health status. Studies on the relationship between dietary diversity scores (DDS) and obesity are inconsistent. Objectives: This study aims to determine the comparison of dietary diversity scores and their relationship with obesity in adolescent girls Methods :The participants in this cross-sectional research were 272 adolescent girls ( 110 obese and 162 normal) aged 12 to 18 years old in West Sumatera. Face-to-face interviews were conducted to determine their sociodemographics, personality traits, dietary diversity score [DDS], and anthropometrics. The DDS was calculated based on five dietary categories [grains/bread, vegetables, fruits, meats and meat substitutes, and dairy items] as well as weight status [BMI Z score]. An independent t test comparing mean DDS between obese and normal groups; an ANOVA test comparing anthropometry based on DDS, both with p < 0.05 significance level. Result : The mean DDS on obesity is significantly lower than normal adolescents by 4.10 ± 1.5 versus 4.46 ± 1.52 p=0.042. Adolescents with lower DDS exhibited obesity of 83.3%, and the normal ones were 16.7%. On the other hand, adolescents with higher DDS showed obesity of 25.6%, and the normal ones were 74.4%. The prevalence of obesity is inversely associated with the dietary diversity score p= 0.012 Conclusion : There was a negatively significant association between dietary diversity score and obesity. In comparison to the normal groups, adolescent girls with obesity had a lower dietary diversity score.